Three-dimensional structures of maturable and abortive capsids of equine herpesvirus 1 from cryoelectron microscopy. - Baker, T S (1990)
Cryoelectron microscopy and three-dimensional computer reconstruction techniques have been used to compare the structures of two types of DNA-free capsids of equine herpesvirus 1 at a resolution of 4.5 nm. "Light" capsids are abortive, whereas "intermediate" capsids are related to maturable intracellular precursors. Their T = 16 icosahedral outer shells, approximately 125 nm in diameter, are indistinguishable and may be described in terms of three layers of density, totalling 15 nm in thickness. The outermost layer consists of protruding portions of both the hexon and the penton capsomers, rising approximately 5 nm above a midlayer of density. The innermost layer, or "floor," is a 4-nm-thick sheet of virtually continuous density except for the orifices of the channels that traverse each capsomer. Hexon protrusions are distinctly hexagonal in shape, and penton protrusions are pentagonal. The structures of the three kinds of hexons (distinguished according to their positions on the surface lattice) are closely similar but differ somewhat in their respective orientations and in the shapes of their channels. The most prominent features of the midlayer are threefold nodules ("triplexes") at the trigonal lattice points. By analogy with other viral capsids, the triplexes may represent trimers of another capsid protein, possibly VP23 (36 kilodaltons [kDa]) or VP26 (12 kDa). Intermediate capsids differ from light capsids, which are empty, in having one or more internal components. In individual images from which the shell structure has been filtered away, these components are seen to have dimensions of 20 to 30 nm but to lack a visible substructure. This material--which is smeared out in the reconstruction, implying that its distribution is not icosahedrally symmetric or necessarily consistent from particle to particle--consists of aggregates of VP22 (46 kDa). From several lines of evidence, we conclude that this protein is located entirely within the capsid shell. These aggregates may be the remnants of morphogenetic cores retained in capsids interrupted in the process of DNA packaging.